Role of Diagnostic procedures in managing human Bacterial infections: A comprehensive overview - Ankurita Bhowmik (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2023)
The study of human illnesses brought on by microbes falls under the wide category of infectious diseases. Among all other challenges, infectious diseases have a profound influence on human existence. From local epidemics to global pandemics, infectious diseases have had a huge impact on civilization growth, country destiny, and human history. Only in the late 1800s did scientists discover that infections are caused by microorganisms, leading to the development of the microbe-specific medical diagnostic technique. If identified and treated properly, many infections have mild consequences. Others, however, including pneumonia and meningitis, etc. can be fatal if neglected. With its capacity to pinpoint the precise source of infection and combat varied and widespread outbreaks, diagnostic procedures play a special role in the management of infectious diseases. Diagnosis-aid therapies work better and help the infected patient avoid long-term consequences. The most appropriate course of medication can also be decided through diagnostic testing. Patients who go undiagnosed may unintentionally spread the illness to others. A prompt diagnosis can thus contribute to the control or prevention of outbreaks. In summary, the novelty and contributions of the study lie in its recognition of the pivotal role played by diagnostic procedures in understanding, managing, and controlling infectious diseases. It also acknowledges the historical discovery of microorganisms as the root cause of infections and the development of specific diagnostic techniques, both of which have had a profound impact on the field of medicine and public health.